Kerosene lamp "kupi": lights the house, but may bring darkness to life - Ahmed, Selim; Hussain, M; Rahman, A; Halim, A; Rahman, F (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):221-5. The abstract of this article is available on the PubMed website